New estimates of the cost of ending poverty and its global distribution - Andrew Sumner; Arief Anshory Yusuf (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This paper makes new estimates of the cost of ending poverty and the global distribution of both the cost and poverty itself. First, the paper discusses definitions of 'ending' poverty, arguing that there is an overemphasis (e.g. SDG 1) on the extreme poverty line which is insufficient for multiple reasons. Second, we turn to the question of the location of global poverty. Although it is commonly noted that global poverty is increasingly located within sub-Saharan Africa and in fragile and conflict-affected states (FCAS), there is a less discussed distribution of global poverty between countries where official development assistance (ODA) matters substantially, and those countries where ODA is no longer financially significant relative to the recipient countries' growing economic size. A new typology of countries is presented based on the intersection of ODA importance vis-à-vis national resources and FCAS/non-FCAS countries. Finally, new estimates are made for the cost of ending global poverty and for the global distribution of that cost and of poverty itself. The paper concludes that (i) the goal of ending poverty ought to be set at least at the 3.65 poverty line if not higher; (ii) approximately half of global extreme monetary poverty, half of global multidimensional poverty, and two thirds of global absolute monetary poverty are located in countries where the importance of ODA is low; (iii) the direct costs of ending extreme and absolute monetary poverty are not prohibitive, respectively 67.1bn and 324.1bn per year in current dollars or 0.12% and 0.56% of the gross national income (GNI) of advanced nations; and (iv) the cost of ending global extreme and absolute monetary poverty is split respectively 50/50 between FCAS and non-FCAS countries; and split respectively 45/55 between countries where ODA matters financially versus countries where ODA is less important. The headline implication for development cooperation is that policy coherence is as important as ODA to ending global poverty.
Keywords: I30; I32; 330; global poverty; SDGs; aid; development finance